Introduction to nursing research : quest for quality nursing - Venzon, Lydia M. (Quezon City : C & E Publishing, 2004)
The books gives simple explanations and examples on the basic process of research so that the students themselves may practice doing these as they learn the steps.
Chapter 1 The need for nursing research -- Chapter 2 Contributions of the sciences to nursing research -- Chapter 3 An overview of the research process -- Chapter 4 Research designs and approaches -- Chapter 5 Collection of data -- Chapter 6 Ethical issues in nursing research -- Chapter 7 Suggested guide for preparing research and thesis proposals -- Chapter 8 Guidelines for the critical reading of a research publication.
Includes index.
Keywords: NURSING -- RESEARCH -- METHODOLOGY; EVIDENCE-BASED NURSING